Desenvolvimento de célula eletrolítica nanoestruturada baseada em mandioca/lítio e eletrodos de nanotubos de carbono - SANTOS, Luís Eduardo de Sena dos (2022)
Carbon is one of the essential elements for life, and it has some allotropic forms. In this work, we will use one of these forms that is the Carbon Nanotube (CNT), because it has characteristics such as: transport electric current with an intensity 100 times higher than copper, retardation in corrosion in electrolytic processes, among others. Thus, the applicability of the CNT has become more evident in the contemporary world through devices such as: sensors, capacitors, batteries, and so on. Through a biodegradable polymer known as starch that is extracted from cassava added to an auto conductivity of the lithium Perchlorate (LiClO_4) that form the electrolyte. Then, it was used of Buckypapers (BP) based on CNT films, whose function is behaves like electrode. In this way, a stack was formed whose dimensions were: 4 cm in length and 2 cm in diameter modeled from the modeling program Cinema 4D version R.14, where the 3D Anet A8 printer was used for the manufacture of the structure of the in which the ABS polymer (Acrylonitrile butadiene styrene) was used as a sheath of the same. Therefore, we obtained satisfactory results through the equipment: scanning electron microscopy (SEM) and electrical characterization of: 0.35 ± 0.003V; 3.18 ± 0.005 kΩ and 0.11 ± 0.001 m A.